How to Stop a Herd of Running Bears? : Market Response to Policy Initiatives during the Global Financial Crisis. (IMF Working Papers; Working Paper ;, 2009)
This paper examines the impact of macroeconomic and financial sector policy announcements in the United States, the United Kingdom, the euro area, and Japan during the recent crisis on interbank credit and liquidity risk premia. Announcements of interest rate cuts, liquidity support, liability guarantees, and recapitalization were associated with a reduction of interbank risk premia, albeit to a different degree during the subprime and global phases of the crisis. Decisions not to reduce interest rates and bail out individual banks in an ad hoc manner had adverse repercussions, both domestically and abroad. The results are robust to controlling for the surprise content of announcements and using alternative measures of financial distress.